Construction of HEK293 and C2C12 cell models transfected by LMNA mutant and related intracellular sublocalization of lamin A/C - TAN Dan-dan, CHAI Jing-yan, LIU Jian-yun, NIE Hong-bing, XIONG Hui, WU Xiang-bin (Jichu yixue yu linchuang, 2020)
Objective To construct an expression vector of fusion protein from wild type LMNA and mutant and the lentivirus vector of LMNA mutant, to study the expression and sublocalization of lamin A/C and the change of nucleus in HEK293 and C2C12 cells. Methods The wild type LMNA was cloned into pEGFP-N1 plasmid to construct pEGFP-N1-LMNA, then pEGFP-N1-LMNA-I373V plasmid for c.1117A＞G site-directed mutant was constructed. The pEGFP-N1-LMNA and pEGFP-N1-LMNA-I373V were transfected respectively into HEK293 and C2C12 cells. Then C2C12 cells were selected with G418 and the sublocalization of GFP-labeled lamin A/C and nuclear morphology were observed under fluorescent microscope. pHBLV-h-LMNA-I373V-3*flag-GFP-PURO was constructed by using pEGFP-N1-LMNA-I373V plasmid as template. After packaging and detecting the titer of pHBLV-GFP-PURO and pHBLV-LMNA-C1117-3*flag-GFP-PURO, C2C12 cells were transfected by the lentivirus. The sublocalization of lamin A/C and abnormal nuclear morphology were examined by immunofluorescence staining. Results The sequences of pEGFP-N1-LMNA, pEGFP-N1-LMNA-I373V and pHBLV-LMNA-C1117-3*flag-GFP-PURO were the same as the target gene. Lamin A/C distributed uniformly at the inner nuclear membrane in HEK293 and C2C12 cells transfected by pEGFP-N1-LMNA, but distributed abnormally, forming distinct aggregates in the cells with transfection of the mutant construct. C2C12 exhibited lower transfection efficiency of plasmid than HEK293. However, transfection efficiency of lentivirus in C2C12 was improved significantly. Lamin A/C forming distinct aggregates in nucleus and abnormal nuclear morphology were also showed in C2C12 after transfection of mutant lentivirus. Conclusions Two kinds of eukaryotic expression vectors of LMNA mutant, and HEK293 and C2C12 cell models transfected by LMNA mutant are successfully constructed, which provides scientific basis for the pathogenesis of diseases caused by LMNA mutant.